Travel in Greek Tragedy - Encinas Reguero, M. Carmen (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2018)
As in Ancient Greek literature in general, travel is a relevant topic in Greek tragedy, not only because many of the preserved tragedies include it in one way or another, but also because it is connected with the nóstos theme and with the anagnórisis scene, which are important elements of tragedy.